(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
The complex and diverse needs of IDPs necessitates urgent need for social welfare programmes that identifies and caters for the peculiar needs of IDPs. The objective of this study was to assess available social welfare programmes and the extent to which they impact on the wellbeing of IDPs. The study adopted case research method. The result showed that IDPs’ based social welfare programmes as a sustainable means of catering for the socioeconomic wellbeing of IDPs in Bakassi was not given adequate attention by government and scholars alike. Instead, the types of social welfare programmes available to IDPs were characterised by spontaneous, ad-hoc, narrow and uncoordinated approaches, leading to myriads of human right abuses, poverty and neglect of Bakassi resettlement camps. Result further revealed that the failure to domesticate social welfare policies and programmes in response to peculiar needs of IDPs was a major setback in the attainment of socioeconomic wellbeing of IDPs. Therefore, government in collaboration with IDPs should develop a realistically domesticated social welfare programme that can address peculiar needs of IDPs, as this would serve as resource for sustained resettlement programmes.